The factors that influence job satisfaction among royal Malaysian customs department employee - Shafi, Muhammad Ammar; Rusiman, Mohd Saifullah; Nor, Maria Elena; Khamis, Azme; Abdullah, Siti Nabilah Syuhada; Azmi, Mohd Syafiq; Zainal Abidin, Munirah Sakinah; Ali, Maselan (2018)
This research aims to spot the factors that influence job satisfaction among Royal Malaysian Customs Department employees. Primary data was used in this research and it was collected from the employees who work in five different departments at Royal Malaysian Customs Department Tower Johor. Those departments were customs department, Internal Taxes, Technical Services, Management and Prevention. The research used stratified random sampling to collect the sample and Structural Equation Modelling (SEM) to measure the relationship between variables using AMOS software. About 127 employees are selected as the respondents from five departments to represent the sample. The result showed that ‘Organizational Commitment’ (p-value = 0.001) has significant and direct effect toward job satisfaction compared to the ‘Stress Condition’ (p-value = 0.819) and ‘Motivation’ factor (pvalue = 0.978). It was also concluded that ‘Organizational Commitment’ was the most influential factor toward job satisfaction among Royal Malaysian Customs Department employees at Tower Custom Johor, Johor Bahru.